Business Models Drive Investor Reactions in Construction Sector - Lili’ Mutala’liah; Nurasik (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the effect of presenting integrated reporting elements in annual reports on investor reactions in building construction companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. Using a quantitative method with multiple linear regression analysis in SPSS version 18, the study analyzed data from 10 purposively sampled companies. Results indicate that the business model element significantly affects investor reactions, while other elements like organizational description, governance, risks and opportunities, strategy and resource allocation, performance, future prospects, and basic elements of disclosure do not. These findings suggest companies should focus on enhancing their business model disclosures to better meet investor expectations and improve market responses. Highlight: Business Model Impact: Only the business model significantly affects investor reactions. Other Elements: Organizational description, governance, etc., show no significant investor impact. Recommendation: Enhance business model disclosures to meet investor expectations. Keyword: Integrated Reporting, Investor Reactions, Building Construction, Indonesia Stock Exchange, Quantitative Analysis